CONTROLLING THE PARAMETERS OF COMPRESSION OF VIDEO FRAMES USING A BITWISE TRANSFORMANTS TRANSMISSION - Баранник, Володимир Вікторович; Твердохліб, Віталій Вікторович; Супрун, Олег Валерійович; Окладной, Дмитро Євгенович (Science-based technologies, 2016)
It outlines the main aspects of the organization of the method of control parameters of compression, in which the transformant considered as the three-dimensional object. This allows controlling the bitrate by bitwise transmission transforman witht truncating a number of bit planes in accordance with the level of the allowable error. As a mechanism for making operating decisions, using dynamic programming method, based on the principle of Bellman's optimality. It provides a way to organize data for this method of control, taking into account the principles of the method of successive approximations technology Progressive JPEG. A mathematical model of the control method presented. Shown the necessity of reducing the number of states of the algorithm and suggests methods that reduce the number of states, thereby increasing the speed of the algorithm based on the division of the transformant according to the degree of difficulty.